IMPACT OF SHORTAGE OF STAFF NURSES ON QUALITY CARE OF PATIENTS AT SPECIALISED HOSPITALS IN LAHORE - MAHMOOD , I; SHAHBAZ , T; FAROOQ , Z; PARVEEN , I; SHARIF , R; MUNIR , S; SHAMOUN , A (Biological and Clinical Sciences Research Journal, 2023)
The nursing shortage has been recognized as a global healthcare issue that can negatively impact the quality of patient care. Adequate staffing of nurses is an essential factor that can ensure the provision of high-quality healthcare services to patients. A shortage of nurses may lead to poor patient outcomes, including medication errors, patient falls, and hospital-acquired infections. Therefore, addressing the nursing shortage is critical to improve patient care and health outcomes. This study investigates the impact of nursing shortage on patient care in healthcare settings. This study used a quantitative cross-sectional descriptive study design to assess the impact of nursing shortage on patient care. The study was conducted in multiple healthcare settings across different regions. A convenience sampling technique was used to select participants for the study. The patients in settings with nursing shortages used and filled out a questionnaire according to international guidelines. The results of the study showed that the majority of the participants reported a negative impact of nursing shortage on patient care. The shortage of nurses was associated with decreased patient satisfaction with nursing staff care. Furthermore, the study found that nursing shortages often led to nurses being overworked and exhausted, leading to medical errors and declining patient quality of care. The study concluded that the nursing shortage significantly negatively impacts patient care in healthcare settings. The shortage of nurses leads to decreased quality of care, increased length of hospital stay, patient mortality rates, and decreased patient satisfaction with care. Therefore, addressing the nursing shortage is crucial for improving patient outcomes and ensuring the provision of high-quality healthcare services.